CLINICAL EVALUATION OF MADHUPRAMEHARI VATI IN THE MANAGEMENT OF APATHYANIMITTAJA PRAMEHA W.S.R. TO DIABETES MELLITUS TYPE II - Kumawat, Naresh Kumar; Bhakuni, Harish; Shankar Mishra, Daya (International Journal of Ayurveda and Pharma Research, 2015)
Type-2 Diabetes Mellitus is a persistent health problem that requires innovative strategies to improve health and needs a multifactorial approach for the treatment. Madhupramehari Vati an Ayurvedic medicine consists of maximum number of Rasayana and Yogvahi drug i.e. Shilajatu (Black Bitumen), Swarnamakshika (Copper Pyrites), Amalaki (Emblica officinalis), Haridra (Curcuma longa) etc. which act as a Naimittika Rasayana. The total number of Patients 33 were divided into two groups named as group A (16 patients of prediabetes or impaired fasting glucose IFG and impaired glucose tolerance IGT clinically diagnosed) was given Madhupramehari Vati 500 mg in tablet form twice a day before taking meal for 60 days and group B (17 patients of diabetics clinically diagnosed) was given Madhupramehari Vati 500 mg with Triphala Kwath of 50 ml twice a day before taking meal for 60 days. The patients were provided a proper diet chart planned according to the classics and to maintain a routine of 30 minutes walk in the morning and in the evening hours, Pranayama daily for 30 min in morning hours. Glycosylated hemoglobin (serum HbA1c) was evaluated in eight patients which showed statistically highly significant results. There were also statistically significant results in the fasting blood sugar (FBS) and post prandial blood sugar (PPBS) parameters, both groups.